Preparation and performance study of a new type of Tile transducer for roadway applications. (October 2020) - Wang, Jun; Cai, Yuanqiang; Liu, Zhiming; Ding, Guangya; Cai, Guojun; Fu, Hongtao
In recent years, piezoelectric technology for recovery of road vibration energy has gained widespread attention. Most research in this field thus far has examined different piezoelectric materials and evaluated their feasibility in field tests, but less attention has been devoted to different transducer structures. In this study, a new type of Tile transducer was developed for roadway applications. The Tile transducer exhibited good vibration absorption effect and energy harvesting efficiency at low-frequency vibration. This study tested the Tile transducer under the supported boundary condition, and analyzed the influence of the curvature of the Tile transducer on the energy harvesting efficiency with regard to the electromechanical conversion performance and structural strength. When the excitation frequency was 10 Hz and load was 500 N, the total power of the Plane transducer was 0.59 mW. Under the same load condition, the total power of the Tile transducer was 15.44 mW, which was 26-fold higher than that of the Plane transducer. An ultimate compressive bearing capacity test and fatigue test of the Tile transducer were then carried out, and the fatigue failure mode was analyzed. The test results prove that the Tile transducer had stable and lasting structural performance.